THE IMPLEMENTATION OF DEBATE TECHNIQUE IN TEACHING SPEAKING AT THE SECOND GRADE STUDENTS OF SMA N 1 SUMBUL - Juan Andrson Siahaan; Rafika Dewi Nasution (REGISTER: Journal of English Language Teaching of FBS-Unimed, 2022)
This research was aimed to identify and describe the process, as well as the problems confronted by teachers and students in learning to speak using debate techniques at the Second Grade Students of SMA N 1 Sumbul. The methodology used in this research was descriptive qualitative. This research used triangulation technique in collecting the data, consists of observations, interviews and questionnaires. After analyzing the data, there are three result points. First, the process of teaching and learning to speak through debate techniques at SMA N 1 Sumbul is not going too well because there are still some problems confronted by both teachers and students. Second, the teacher encountered several difficulties in teaching speaking out through debate technique, such as educators continuing to use their local tongue and the teacher being unable to manage a class that was overcrowded and necessitating extensive preparation to ensure that learning with this debate technique ran smoothly. Third, students' difficulties in learning to speak via debate approach included being unable to express anything in their main language, needing more preparation time to build their statements when building the case, and being unable to manage their emotions when delivering opinions. Key words: Descriptive Qualitative Research, Speaking, Debate technique